Screening for Depression among Elderly Population in Pune City - Anagha P Jadhav; Sunil M Sagare (Medsci Publications, 2019)
Background: The Indian aged population is the second largest in the world. A high prevalence of mental disorders is a major public health problem with a global prevalence of 322 million; with India contributing to 31 million. The prevalence in elderly population var- ies from 13 to 25%. Early diagnosis and treatment are the key step towards curbing this mental health problem. We screened the el- derly population for depression to determine the prevalence and to identify the risk factors of depression in elderly urban population in Pune city. Material and Methods: A cross sectional study was conducted on 242 elderly subjects >60 years by administering the WHO (five) wellbeing index and the major International Classification of Dis- eases 10th Revision. Results: The prevalence of depression was 21.07%. On analysis, age more than 80 years (p value 0.004, Odds ratio- 2.84,95% CI; 1.38- 5.68), female gender (p value 0.03, Odds ratio- 1.94,95% CI; 1.03- 3.64), loneliness (p value 0.001, Odds ratio- 2.56,95% CI; 1.50-5.27) and financial dependence (p value 0.001, Odds ratio- 3.17,95% CI; 1.53- 6.55) were statistically significantly associated with depres- sion. Conclusion: The prevalence of depression was 21.07%. The major risk factors identified were age more than 80 years, loneliness and financial dependence.